Presentation of a Translators’ Training Programme Focusing on Economics and Law - AKPACA, SERVAIS MARTIAL (My University, 2022)
The aim of this paper is to discuss the contents of a translator training programme for the African region, especially West Africa. After making an update on the translator profile and the translator competence, using both a deductive and a descriptive approach, the paper has developed a curriculum comprising elements of core knowledge as well as specialised knowledge, research methods and general knowledge. Core knowledge comprises the theory and history of translation studies, linguistics and specialised translation. The area of specialism is made up of law and economics lectures, reading comprehension exercises, writing skills, bilingual oral communication, and terminology lectures. Scientific research methodology focuses on research approaches in Translation Studies. Research approaches include qualitative and/or quantitative research, conceptual research, evaluative research, context-oriented translation, participant oriented translation, translation as a process, translation as a product, critical discourse analysis, etc. General knowledge enhances students’ language skills and knowledge of both French and English speaking countries’ civilisations and cultures. The main findings are that translator competence is essentially a system of operational rather than declarative knowledge; translator profile depends on the labour market demands; the constructivist approach to education is more convenient in a translation training programme; students’ evaluation should be both formative and summative.
Keywords: Training Programme; Translator Profile; Translator Competence; Evaluation; Africa